Television and Growing Up The Impact of Televised Violence. Report to the Surgeon General United States Public Health Service. - Surgeon General's Scientific Advisory Committee on Television and Social Behavior, Washington, DC.; Surgeon General's Scientific Advisory Committee on Television and Social Behavior, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
A request by Senator John O. Pastore for an inquiry into the effect of televised crime and violence and anti-social behavior by individuals resulted in the formation of the Scientific Advisory Committee on Television and Social Behavior. The committee report consists of the conclusions reached by 12 behavioral scientists after a review of 40 original research reports and of previously available literature on the effects of televised violence on the tendency of children toward aggressive behavior. The committee considered two major sources of evidence on effects of viewing violence and aggression on TV: evidence from experimental studies, and evidence from surveys. The two sets of findings were found to converge in three respects: "a preliminary and tentative indication of a causal relation between viewing violence on TV and aggressive behavior; an indication that any such causal relation operates only on some children (who are predisposed to be aggressive); and an indication that it operates only in some environmental contexts." The committee also identified areas for future research. (SH)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (1972-0-453-851, $2.25).
Sponsoring Agency: Public Health Service (DHEW), Rockville, MD.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Aggression; Children; Environmental Influences; Programing (Broadcast); Television; Television Research; Television Surveys; Television Viewing; Violence